Antibacterial and Antioxidant Activities of Fungal Endophytes Isolated from Medicinal Plants in Simeulue Island, Aceh - Ahmad Fathoni; Muhammad Ilyas; Praptiwi; Dewi Wulansari; Andria Agusta (HAYATI Journal of Biosciences, 2022)
Natural products from endophytic fungi have a wide range of medicinal applications, including antibacterial and antioxidant agents. The research aimed to evaluate the antibacterial and antioxidant activities of compounds derived from endophytic fungi isolated from medicinal plants collected from Simeulue Island by TLC dot-blot and microdilution assays. Eighty-one fungal extracts were screened for antibacterial and antioxidant activities. Antibacterial activity was evaluated against Gram-positive and negative bacteria, i.e., Staphylococcus aureus InaCC B-4 and Escherichia coli InaCC B-5, respectively. Antioxidant activity was carried out by using free radical scavenging of 1,1-diphenyl-2-picrylhydrazyl (DPPH). The results of the TLC bioassay revealed that the fungal extracts have activities as antibacterial and antioxidant are 65 (against S. aureus), 57 (against E. coli), and 48 extracts (DPPH free radical scavenger). Two extracts, Phomopsis sp. 48BtSi-2.1 and Xylaria sp. 55DnSi-1.1, showed strong antibacterial activity against S. aureus with MIC value of 32 μg/ml. Furthermore, nine extracts (Schizophyllum sp. 20DnSi-1; Hyphomycetes 36BhSi-1.1; Phomopsis sp. 36DnSi-2.1; Schizophyllum sp. 39DnSi-1.1; Xylaria sp. 39RpSi-2.1; Phomopsis sp. 41BtSi-1.1; Phomopsis sp. 48BtSi-2.1; Lasiodiplodia sp. 48BtSi-3.1; Schizophyllum sp. 50DnSi-3) were strong activity against E. coli with MIC value ranges from 32 to 64 μg/ml. One extract, Xylaria sp. 04BtSi-2.2 has strong antioxidant activity as DPPH free radical scavenger with an IC50 value of 21.66 μg/ml (AAI value of >1).